Analisis Hukum Tentang Disparitas Pidana Dalam Kasus Tindak Pidana Korupsi Penyalahgunaan Wewenang Proyek Pengerjaan Jalan (Pada Kasus Putusan Nomor 54/Pid.Sus/Tipikor/2013/PN.PBR) - Aditias, Akfini; Efendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Corruption is one part of a special criminal law. Corruption is considered detrimental to the social and economic rights of Indonesian society. The seriousness of the government in tackling corruption is the establishment of Law No. 31 of 1999 in conjunction with Law No. 20 Year 2001 on Corruption Eradication. The purpose of this thesis, namely; First, to determine the process of proving corruption in road construction projects abuse of authority in case No. 54/Pid.Sus/Corruption/2013/PN.PBR, Second, To know the legal consideration by the judge in the case No.54/Pid.Sus/Corruption/2013/PN.PBR.This type of research can be classified into types of normative research, because in this study the authors conducted a study and discussion or analysis in depth against Corruption Court decision No.54/Pid.Sus/Corruption/2013/PN.PBR, sources of data, which is used , primary data, secondary data, and the data tertiary data collection techniques in this study using literature studies or studies documentary.From the research, there are two fundamental problems that can be inferred. First, That the proof in case number 54 / Pid.Sus / Corruption / 2013 / PN.PBR is using negative verification system (negatief etterlijk), where the burden of proof remains with the Prosecution, while the defendant merely presenting defense witnesses only (adecharge). Secondly, That the legal reasoning by judges in adjudicating the case number 54 / Pid.Sus / Corruption / 2013 / PN.PBR is not true, where the judge only consider the guilt of the accused of the charges of the subsidiary that Article 3 of Law No. 31 Year 1999 jo Law Law No. 20 of 2001 without first considering in detail where the location of the non-fulfillment element of Article 2 of Law No. 31 of 1999 in conjunction with Law No. 20 of 2001. Because if Article 2 is not proven then automatically Article 3 also should not be proven according to law because both elements are almost the same article that is committed an unlawful act. Suggestions author, First, it is suggested to the Public Prosecutor and the judge who tried the case number 54/Pid.Sus/ Corruption/2013/PN.PBR that in the proof should be done with a combination of negative evidence of proof, so that the handling of this case actually achieve sense of justice. Second, it is suggested to the judge who tried the case number 54 / Pid.Sus / Corruption / 2013 / PN.PBR to first consider which elements are not met from the Article 2 of Law No. 31 of 1999 in conjunction with Law Number 20 Year 2001, because otherwise they will give the impression of judges chose a lesser sentence with direct consideration of Article 3 of Law No. 31 of 1999 in conjunction with Law No. 20 of 2001.Keywords: corruption - proof - consideration of the judge